Treatment Choices in Managing Bethesda III and IV Thyroid Nodules: A Canadian Multi-institutional Study. Issue 2 (June 2021) - Kuta, Victoria; Forner, David; Azzi, Jason; Curry, Dennis; Noel, Christopher W.; Munroe, Kelti; Bullock, Martin; McDonald, Ted; Taylor, S. Mark; Rigby, Matthew H.; Trites, Jonathan; Johnson-Obaseki, Stephanie; et al.
Objective: Patient-centered decision making is increasingly identified as a desirable component of medical care. To manage indeterminate thyroid nodules, patients are offered the options of surveillance, diagnostic hemithyroidectomy, or molecular testing. Our objective was to identify factors associated with decision making in this population. Study Design: This is a retrospective cross-sectional study of patients with Bethesda III and IV thyroid nodules. Setting: Multi-institutional. Methods: Factors of interest included age, sex, socioeconomic status (SES), nodule size, institution, attending surgeon, surgeon payment model, and hospital type. Our outcome of interest was the initial management decision made by patients. Results: A total of 956 patients were included. The majority of patients had Bethesda III nodules (n = 738, 77%). A total of 538 (56%) patients chose surgery, 413 (43%) chose surveillance, and 5 (1%) chose molecular testing. There was a significant variation in management decision based on attending surgeon (proportion of patients choosing surgery: 15%-83%; P ≤.0001). Fee-for-service surgeon payment models (odds ratio [OR], 1.657; 95% CI, 1.263-2.175; P < .001) and community hospital settings (OR, 1.529; 95% CI, 1.145-2.042; P < .001) were associated with the decision for surgery. Larger nodule size, younger patients, and Bethesda IV nodules were also associated with surgery. Conclusion: While it seems appropriate that larger nodules, younger age, and higher Bethesda class were associated with decision for surgery, we also identified attending surgeon, surgeon payment model, and hospital type as important factors. Given this, standardizing management discussions may improve patient-centered shared decision making.